Pengaruh Pengalaman Kerja, Komitmen Profesional Terhadap Pengambilan Keputusan Etis Auditor pada Kantor BPK Provinsi Sulawesi Selatan - Andi Sri Kumala Putri P Mala; Iwan Kurniawan; Amrizal Salida (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the attitude of an auditor towards decision making in carrying out the profession as a public accountant. issues regarding the ethics of accountants develop as ethics violations occu, both conducted by public accountants, internal accountants and government accountants. Examples of auditor cases, the case that befell Kantor Akuntan Publik (KAP) Mitra Winata and friend Happened in 2007. minister of finance (Menkeu) Sri Wahyuni Indrawati dikarenakan akuntan publik tersebut telah melakukan pelanggaran terhadap Standar Professional Akuntan Publik (KAP) Petrus Indra Winata, because the public accountant has committed a violation of the Professional Standards of Public Accountants (SSAP) Violations committed related to the audit of the financial statements of PT Muzatek Jaya last financial year 31 December 2004. The existence of the above case should provide awareness for the Auditor to apply the Professional Standards of Public Accountants in carrying out the accountant profession. Therefore, the theme of independence, ethics and decision making in the accounting profession also has a very important and deep understanding in maintaining the reputation of the accounting profession. Based on the reasons above this study takes the title "Influence of Work Experience, Professional Commitment to Auditor's Ethical Decision Making"